PECAHAN TEMPURUNG KELAPA SEBAGAI AGREGAT KASAR PADA BATAKO - Albert; Suryanto (Politeknik Sampit, 2022)
So far, many industrial waste materials such as onyx sand, iron lathe fiber that have not been used optimally have been used as research materials as added materials in the manufacture of building materials and get pretty good results. One of the wastes that has not been utilized optimally is coconut shell wasteThis study aims to determine the effect of adding coconut shell fragments to the compressive strength of bricks and polynomial regression of the relationship between variations in coconut shell fragments and the compressive strength of bricks.The method used in this study was to conduct research at the Laboratory of the Faculty of Engineering, University of Muhammadiyah Palangkaraya with variations in the addition of coconut shell fractions 0%, 2%, 4% and 6%.The test object of brick sized 40x20x10 cm. The variation of the experimental objects of brick without coconut shell, and brick with coconut shell is 2%, 4%, 6%. The tests included the compressive strength of the bricks with variations of 0%, 2%, 4%, and 6% with a curing of 28 days. the use of coconut shells of nipah fiber as a partial replacement of cement for the compressive strength of bricks has an average value that has increased successively. The average value of the compressive strength of bricks is with variations in the addition of 0% palm fiber coconut shell of 20.09 kg/cm2 or 1.1760 MPa with a mixture of 2% palm fiber coconut shell of 21.70 Kg/cm² or 1.2847 MPa, with a mixture of 4% nipa palm fiber coconut shell at 28.73 Kg/cm² or 1.7710 MPa, and with a 6% palm fiber coconut shell mixture of 30.94 Kg/cm² or 1.9272 MPa. And the optimum level of coconut shell nipah fiber against the compressive strength of the brick mixture is a variation of 6%